Optic Nerve Head Hemorrhages Associated With Posterior Vitreous Detachment. Issue 2 (March 2018) - Polkinghorne, Philip J.
Abstract : Purpose: : To report and evaluate the clinical and optical coherence tomography (OCT) features of optic nerve hemorrhages (ONH) associated with spontaneous posterior vitreous detachment (PVD). Design: : A prospective case series conducted at a private ophthalmic practice in Auckland, New Zealand. Methods: : A consecutive series of patients presenting at a private multispecialty practice in Auckland, New Zealand, with symptoms of PVD with ONH underwent imaging of the optic nerve with digital retinal photography and OCT. The number and location of each hemorrhage were recorded, together with relevant ophthalmic and demographic data. Results: : Twenty of 30 eyes with ONH had evidence of persistent vitreopapillary adhesion. Three patterns of adhesion were identified: central, peripheral, and combined. In all, 52 hemorrhages were identified, of which the majority were flame‐shaped, although other types were seen including dot and blot hemorrhages. One subretinal hemorrhage occurred in a patient with a central vitreopapillary adhesion. Conclusions: : ONH hemorrhages associated with PVD are commonly found with persistent vitreopapillary adhesions as evidenced on OCT. The clinical features of ONH together with OCT imaging may help to distinguish ONH associated with PVD from other hemorrhages found on or adjacent to the optic nerve.